The Birth Weight of Newborns from Different Environments - Wojtowicz, Ewa (Anthropological Review, 1996)
The birth weight of 1,210 newborns born in 1993-1994 from ecologically „clean” (Kościerzyna) and ecologically risky regions (Puck) was analyzed. Birth weight is about 70 g lower in the risky than in the „clean” region.